Prevalence of Middle Ear Infections and Associated Risk Factors in Children under 5 Years in Gasabo District of Kigali City, Rwanda - Kaitesi Batamuliza Mukara; Richard J. Lilford; Debara Lyn Tucci; Peter Waiswa (International Journal of Pediatrics)
Middle ear infections are common in children, and delay in diagnosis and treatment may result in complications such as delays in speech and language development and deafness. The aim of this study was to determine the prevalence and care seeking behaviour for middle ear infections in children under five years in Kigali city. We conducted a cross-sectional study among 810 children aged 6–59 months in Gasabo district of Kigali city, Rwanda. The prevalence of middle ear infections was 5.8%, of whom 4% had chronic suppurative otitis media. A child was less likely to develop middle ear infections if they lived in an urban setting (OR = 0.52, 95% CI: 0.285–0.958) but more likely to develop middle ear infections if exposed to household smoke (OR = 2.54, 95% CI: 1.18–5.46). Parents were unlikely to know that their child had an ear infection (OR: 0.15, 95% CI: 0.06–0.34). Middle ear infection remains a public health problem in Rwanda but many parents were not aware of its presence in the affected children. There is a need to raise awareness of parents about ear infection and to promote early care seeking from qualified health workers.